Le désaccord travesti dans la comédie de mœurs de Molière : dialogisme et polyphonie - Frédérique SAEZ (Corela)
As a follow up to previous searches, the aim of this article is to examine another phenomenon of veiled disagreement that is to say : the disguised disagreement. It is about the cases where a speaker suggests a point of view that is not congruent with regard to previous (or posterior) elements. This type of ‘suitable disagreement’, frequently used in the comedy of morals by Molière, imposes on the interlocutor (the character listening) – and to the audience – a complex operation of decoding, or even of co-statement in the case of disguised disagreement. We thus opted for a praxematic approach which reports at the same time cotextual phenomena (linguistic and/or periverbal) and verbal interactions, by trying to highlight the mechanisms of production and interpretation of this disagreement by the analysis of the markers (linguistic and/or periverbal) that allow for the interpretation of a dissensus. These markers fall essentially within the phenomena of dialogism and polyphony, central elements in the case of disguised disagreement. More generally we tried to highlight the discursive strategy organized by the speaker and the various cognitive roles of the receivers.